The impact of cash transfers on food security in sub-Saharan Africa: evidence, design and implementation - Francesco Burchi; Christoph Strupat (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
One of the priorities of the international community is alleviating food insecurity, as stated in Goal 2 of the recently approved 2030 Agenda: End hunger, achieve food security and improved nutrition and promote sustainable agriculture. The region with the highest prevalence of food insecurity is sub-Saharan Africa (SSA); most of the efforts must be concentrated there. Food insecurity is mostly widespread among rural households who have either no land or only small plots, and who live in conditions of extreme poverty. Traditional agricultural/ economic interventions alone are unlikely to generate substantial improvements, as they are rarely specifically targeted to the poor. Yet social protection schemes, in particular the emerging cash transfers (CTs), have great potential. Evidence shows, however, that while these measures effectively expand food consumption and asset accumulation, thereby increasing households' resilience, CTs must be linked to other interventions in order to sustainably graduate households out of food insecurity. What lessons can we learn from the empirical evidence in the region? · CTs have proven to be an effective tool for increasing households' calorie intake. Therefore, policy-makers should use them, particularly in this region. · International organizations, bilateral donors and national policy-makers should pay attention to four major design features of CT programmes: 1. Targeting: Some CTs do not reach the expected population and therefore have little effect on food security. CTs can use different targeting mechanisms: There is no one-size-fits-all solution. 2. Regularity of payments: Cash disbursements must be regular so that households can plan. Wherever several delays were experienced, the CTs were ineffective. 3. Transfer size: Monetary transfers should be at least equal to 20% of consumption by the poor. No positive benefits in terms of food security were detected when the amount of the transfer was below this threshold. However, CTs should not be large enough to increase social inequality and discourage work. 4. Political support: To ensure positive long-term effects and for beneficiaries to perceive them as regular programmes, CTs must be backed by strong political support. In SSA, programme ownership is often missing. · CTs alone cannot positively impact nutrition knowledge and nutrition/hygienic practices, and have been shown to have limited effects on diet and nutrition. In order for CTs to have long-lasting effects on nutrition, they must be complemented by other interventions such as nutrition education, food supplementation for vulnerable groups and specific economic policies. Ethiopia's Productive Safety Net Programme (PSNP) offers an innovative model for connecting these policies. · Although it is not generally advisable to condition CTs to beneficiaries' fulfilment of certain requirements, introducing soft conditions that link attendance at nutrition education courses to receiving CTs should be considered in SSA because they do not cost much or require large monitoring capacities.
Keywords: 330; Armut und Ungleichheit; Soziale Sicherung und Inklusion